2015
DOI: 10.1037/xge0000065
|View full text |Cite|
|
Sign up to set email alerts
|

The propagation of self-control: Self-control in one domain simultaneously improves self-control in other domains.

Abstract: A rich tradition in self-control research has documented the negative consequences of exerting self-control in one task for self-control performance in subsequent tasks. However, there is a dearth of research examining what happens when people exert self-control in multiple domains simultaneously. The current research aims to fill this gap. We integrate predictions from the most prominent models of self-control with recent neuropsychological insights in the human inhibition system to generate the novel hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 99 publications
(229 reference statements)
7
95
0
1
Order By: Relevance
“…Such findings would presumably get high priority for publication. The handful that have been published (e.g., Apfelbaum and Sommers, 2009; DeWall et al, 2011; Carter and McCullough, 2013a; Tuk et al, 2015) reflect highly unusual, specifically designed circumstances. For example, DeWall et al (2011) found that leaders often disdained low-level work, but when they were depleted, they ceased to assess whether tasks were suitable for them and simply did their best on everything, resulting in an improvement compared to non-depleted leaders.…”
Section: Nothing or Something?mentioning
confidence: 99%
“…Such findings would presumably get high priority for publication. The handful that have been published (e.g., Apfelbaum and Sommers, 2009; DeWall et al, 2011; Carter and McCullough, 2013a; Tuk et al, 2015) reflect highly unusual, specifically designed circumstances. For example, DeWall et al (2011) found that leaders often disdained low-level work, but when they were depleted, they ceased to assess whether tasks were suitable for them and simply did their best on everything, resulting in an improvement compared to non-depleted leaders.…”
Section: Nothing or Something?mentioning
confidence: 99%
“…The lack of a main effect of ego depletion on food consumption is consistent with recent research (Carter et al, 2015). Some researchers have contended that the ego depletion effect is substantially smaller than published literature implies (Carter and McCullough, 2013, 2014; Tuk et al, 2015; see Hagger and Chatzisarantis, 2014, for a response to this argument). Some researchers have questioned the authenticity of the depletion effect (Carter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…we performed conceptual replications). Such an approach is more informative than the test of a single paradigm (Tuk, Zhang, & Sweldens, 2015) and allows examining whether a possible underlying effect is restricted to a certain measure or generalizes across several measures. Because the moderation hypothesis seemed a plausible alternative to the main-effect hypothesis, we included subjective SES as a possible moderator for the second half of our studies and conducted further studies online to increase the samples' variance on subjective SES.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Because tests for heterogeneity and moderators tend to be underpowered with small amounts of studies (k < 20; Huedo-Medina, Sánchez-Meca, Marín-Martínez, & Botella, 2006), we set the alpha level for both tests to .10 (Tuk et al, 2015). Furthermore and as an additional criterion for heterogeneity that is independent of the included number of studies, we applied I 2 > 50% as a criterion for heterogeneity (Braver et al, 2014).…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation